The effectiveness of CBT approaches on big five personality and internet aggression among undergraduate students: A single subject study - Teoh, Wen Qi (2023)
There is a growing concern that undergraduates are more likely to be associated with certain Big Five Personality characteristics that are associated with an increased risk of developing aggressive internet behaviours. Thus, this research objective is to observe the effectiveness Cognitive Behavioural Therapy (CBT) approaches in affecting Big Five Personality (BFP) characteristics and Internet Aggression among undergraduate students. This research is a single subject study conducted in a university counselling room in Malaysia which only has 1 Chinese male undergraduate participant. Purposive sampling was selected to identify groups of undergraduate students that are especially knowledgeable about or experienced with the criteria of this research. The instruments implemented for quantifying the variables were Buss-Perry Aggression Questionnaire (BPAQ) and Big Five Inventory (BFI). The researcher administered the pre-test to the participant during the screening process and the post-test after the last session of intervention. Based on the results, CBT showed positive effect on Internet Aggression scores and symptoms which had substantial 12-points reduction. However, CBT showed less significant effect on shifting the BFP scores of the participant with a maximum of 4-points changes in Openness, Conscientiousness, Agreeableness and Neuroticism, while only a single point reduction for Extraversion. In conclusion, this research findings shows that the components and approaches of CBT bring changes towards thoughts and behaviours which associated with Internet Aggression issues. The present research functions as a basis for future research by extensively contributing to existing literature and advancing understanding of CBT approaches on a target sample of Malaysian undergraduate students